Adding colchicine to tocilizumab in hospitalized patients with severe COVID-19 pneumonia: An open-label randomized controlled trial. Issue 39 (30th September 2022) - Rahhal, Alaa; Najim, Mostafa; Aljundi, Amer Hussein; Mahfouz, Ahmed; Alyafei, Sumaya Mehdar; Awaisu, Ahmed; Habib, Mhd, Baraa; Obeidat, Ibrahim; Faisal, Mohanad Mohammed; Alanzi, Meshaal Ali; Nair, Arun Prabhakaran; Elhassan, Areeg; et al.
Abstract : Introduction: Colchicine acts upstream in the cytokines cascade by inhibiting the nod-like receptor protein 3 (NLRP3) inflammasome while interleukin 6 (IL-6) receptor antagonists, such as tocilizumab, block the end result of the cytokines cascade. Hence, adding colchicine to tocilizumab with the aim of blocking the early and end products of the cytokines cascade, might reduce the risk of developing cytokine storm. Methods and analysis: We aim to conduct an open-label randomized controlled trial to evaluate the efficacy and safety of adding colchicine to tocilizumab among patients with severe COVID-19 pneumonia to reduce the rate of invasive mechanical ventilation and mortality. We will include patients with severe COVID-19 pneumonia who received tocilizumab according to our local guidelines. Enrolled patients will be then randomized in 1:1 to colchicine versus no colchicine. Patients will be followed up for 30 days. The primary outcome is the rate of invasive mechanical ventilation and will be determined using Cox proportional hazard model. Discussion: Given colchicine's ease of use, low cost, good safety profile, and having different anti-inflammatory mechanism of action than other IL-6 blockade, colchicine might serve as a potential anti-inflammatory agent among patients with severe COVID-19 pneumonia. This study will provide valuable insights on the use of colchicine in severe COVID-19 when added to IL-6 antagonists. Ethics and dissemination: The Medical Research Center and Institutional Review Board at Hamad Medical Corporation in Qatar approved the study protocol (MRC-01-21-299). Results of the analysis will be submitted for publication in a peer-reviewed journal.